PERBEDAAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK BERDASARKAN JENIS KELAMIN PADA PEMBELAJARAN MIND MAPPING KELAS XI SMA NEGERI 9 GOWA - Muhammad Putra Prasetyo (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This research was a quasi-experimental study which aims to find out the differences in students' creative thinking skills based on sex difference in mind mapping class XI SMA Negeri 9 Gowa. This study used a pretest-posttest nonequivalent control group design with 2 x 2 factorial pattern. This research sample was determined by random sampling technique. The independent variable in this study was mind mapping learning while sex difference was a moderator variable. The dependent variable was creative thinking skills measured by using essay tests. Data were analyzed with anacova. The results showed that 1) mind mapping influenced the improvement of students 'creative thinking skills: 2) sex difference did not affect the students' creative thinking skills, which meant that both sexes had the same potential in increasing their creative thinking skills; 3) the interaction between mind mapping and sex difference did not affect the improvement of students' creative thinking skills.